ETHICS OF SUSTAINABILITY: USING MAQASHID AL-SHARIA TO GUIDE NATURAL RESOURCE MANAGEMENT IN ALGERIA - Ben Gharbi, Houria; Abushaala, Ismail (I-Economics, 2025)
Natural wealth in resources, if not managed well, is likely to lead to environmental degradation, economic vulnerability, and social injustices, as in the majority of resource-endowed nations, including Algeria.  This research examines the degree to which Maqasid al-Sharia, can act as ethical guidelines in sustainable management of resources.It uses a qualitative descriptive-analytical method in examining Algerian policies on the five maqasid: religion, life, intellect, lineage, and money.  Although Algeria has initiated various policies, ranging from safeguarding the environment, water security, to economic diversification, their actualization is constrained by poor governance, delayed energy transition, and failure in integrating ethical principles. Conclusions from comparative experience of Muslim resource-dependent nations are that mainstreaming faith values in modern-day governance improves sustainability, accountability, and intergenerational justice. The conclusion is to present a composite approach that integrates Islamic moral values and policy instruments towards better stewardship of Algerian natural resources.